2020
DOI: 10.1017/s1479262120000301
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yield of safflower (Carthamus tinctoriusL.) genotypes under semi-arid conditions

Abstract: To identify appropriate genotypes for breeding varieties suitable for semi-arid areas, yield components, as well as morphophonological traits of 127 safflower genotypes, were assessed at the Seed and Plant Improvement Institute, Iran. Cluster analysis revealed four distinct groups. The largest group (third cluster) includes 48 genotypes with characteristics such as mostly yellow-coloured flowers, mostly thorny with few thistle genotypes, relatively early-flowering, relatively high number of heads and grains pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
1
2
0
Order By: Relevance
“…High flower production and stigma yield are the results of early flowering. This significant and negative correlation between phenological and productive traits is observed also in other crops, such as Salvia hispanica L. [50], Cucumis sativus [51], Carthamus tinctorius L. [52], and Digitaria exilis [53].…”
Section: Discussionsupporting
confidence: 52%
“…High flower production and stigma yield are the results of early flowering. This significant and negative correlation between phenological and productive traits is observed also in other crops, such as Salvia hispanica L. [50], Cucumis sativus [51], Carthamus tinctorius L. [52], and Digitaria exilis [53].…”
Section: Discussionsupporting
confidence: 52%
“…It presents a substantial challenge to the sustainability of agriculture [67]. For this reason, studying the genetic diversity of safflower could provide valuable information on germplasm maintenance and utilization for breeders to improve breeding programs for semi-arid areas to ensure sustainable crop production [68,69].…”
Section: Discussionmentioning
confidence: 99%
“…There is a positive and significant correlation between 1000 seed weight and seed yield. The 1000 seed weight is an important selection criterion that has an indirect effect on improving seed yield in safflower (Arslan, 2007a, b; Camaş & Esendal, 2006; Karimi et al, 2013; Mousavi Ojaq et al, 2020; Sirel & Aytac, 2016). Studies have shown that the 1000 seed weight in safflower varies between 24.7 and 47.8 g (Erbaş et al, 2016), 27.0 and 55.8 g (Arslan & Culpan, 2018), 21.7 and 53.1 g (Ali et al, 2020), 35.2 and 46.9 g (Arslan & Culpan, 2020), 38.0 and 41.0 g (Licata et al, 2023) and shows a wide variation.…”
Section: Resultsmentioning
confidence: 99%